Ice Breaking Method as Communication Strategy of Family Hope Program (PKH) Facilitators in Strengthening Relationships with the Community (Case Study: Communication Strategy of Facilitators to PKH Beneficiaries (PM) at RT 003 RW 001, Aren Jaya Village, East Bekasi District) - Asih, Putri Sekar; Lenggana, Wulan Furrie (Riwayat: Educational Journal of History and Humanities, 2024)
The communication strategy is designed as an effort by the Family Hope Program (PKH) facilitator to build effective communication with the community to strengthen relationships with the community, especially with beneficiaries (PM) of PKH social assistance. This study aims to determine the extent to which the communication strategy of PKH facilitators is implemented in strengthening relationships with the community using the ice-breaking method, the obstacles faced, and efforts to resolve these obstacles. This study uses a qualitative approach. The data obtained were through observation, interviews, and documentation with research subjects, namely PKH facilitators and PKH social assistance recipients with the research location in the community in the RT 003 RW 001 area of Aren Jaya Village, East Bekasi District. The study results showed that PKH facilitators used communication strategy steps to strengthen relationships with the community during P2K2 by adjusting the way of delivering education and selecting the type of ice-breaking to be given. PKH facilitators provide information that is easy for the community to understand. Small ice-breaking activities lighten the mood and build familiarity between PKH facilitators and the community. The communication strategy of PKH facilitators to strengthen relationships with the community through the ice-breaking method is concluded to strengthen relationships within the group, foster active participation of participants during P2K2 activities, and help the community understand the P2K2 lesson messages delivered by PKH facilitators.